Scholastic student thesaurus - Bollard, John K. (New York : Scholastic Reference, 2002)
Provides synonyms and antonyms for thousands of English words.
English Language & Literature.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms